2002
DOI: 10.1515/znb-2002-0204
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study on the Structure of Nitramide H2NNO2

Abstract: Computational Chemistry, Nitramide, Intermolecular Hydrogen Bond Nitramide was investigated by multinuclear NMR spectroscopy, X-ray-diffraction and computational methods. The crystal structure analysis at various temperatures reveals a planar conformation of the molecule with a N-N bond length corresponding to a bond order between one and two. Hydrogen bonds connect the nitramide molecules side-on and end-on. This leads to the formation of layers in the crystal. Calculations were performed to explain the short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The UV absorption spectrum of nitramide has been obtained in the crystal, in the solution, ,3a and in the gas phase 3b. The gas-phase spectrum exhibits a moderate band centered around 6.3 eV.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The UV absorption spectrum of nitramide has been obtained in the crystal, in the solution, ,3a and in the gas phase 3b. The gas-phase spectrum exhibits a moderate band centered around 6.3 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the solution spectrum presents two weak shoulders under 5.0 eV . The theoretical assignment has been accomplished by several authors by using different theoretical approaches. Both Stals et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was found that under acidic conditions the N ‐alkyl nitramines, RHNNO 2 , undergo the same type of decomposition reaction as the parent nitramine, but not under basic conditions. Also, nitramines and their catalyzed decomposition reactions have been the subjects of several computational studies …”
Section: Figurementioning
confidence: 99%